Rapid assessment of the biodiversity impacts of the 2019–2020 Australian megafires to guide urgent management intervention and recovery and lessons for other regions. (21st October 2021) - Legge, Sarah; Woinarski, John C. Z.; Scheele, Ben C.; Garnett, Stephen T.; Lintermans, Mark; Nimmo, Dale G.; Whiterod, Nick S.; Southwell, Darren M.; Ehmke, Glenn; Buchan, Anne; Gray, Jenny; Metcalfe, Dan J.; et al.
Abstract: Aim: The incidence of major fires is increasing globally, creating extraordinary challenges for governments, managers and conservation scientists. In 2019–2020, Australia experienced precedent‐setting fires that burned over several months, affecting seven states and territories and causing massive biodiversity loss. Whilst the fires were still burning, the Australian Government convened a biodiversity Expert Panel to guide its bushfire response. A pressing need was to target emergency investment and management to reduce the chance of extinctions and maximise the chances of longer‐term recovery. We describe the approach taken to rapidly prioritise fire‐affected animal species. We use the experience to consider the organisational and data requirements for evidence‐based responses to future ecological disasters. Location: Forested biomes of subtropical and temperate Australia, with lessons for other regions. Methods: We developed assessment frameworks to screen fire‐affected species based on their pre‐fire conservation status, the proportion of their distribution overlapping with fires, and their behavioural/ecological traits relating to fire vulnerability. Using formal and informal networks of scientists, government and non‐government staff and managers, we collated expert input and data from multiple sources, undertook the analyses, and completed the assessments in 3 weeks for vertebrates and 8 weeks for invertebrates. Results: The assessments prioritised 92 vertebrate and 213 invertebrate species for urgent management response; another 147 invertebrate species were placed on a watchlist requiring further information. Conclusions: The priority species lists helped focus government and non‐government investment, management and research effort, and communication to the public. Using multiple expert networks allowed the assessments to be completed rapidly using the best information available. However, the assessments highlighted substantial gaps in data availability and access, deficiencies in statutory threatened species listings, and the need for capacity‐building across the conservation science and management sectors. We outline a flexible template for using evidence effectively in emergency responses for future ecological disasters.